2019
DOI: 10.1115/1.4042734
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Simulation on Imbibition of the Residual Fracturing Fluid in Tight Sandstone Reservoirs

Abstract: Fracturing is a fundamental technique for enhancing oil recovery of tight sandstone reservoir. The pores in tight reservoirs generally have small radii and generate tremendous capillary force; accordingly, the imbibition effect can significantly affect retention and absorption of the fracturing fluid. In this study, the imbibition behaviors of the fracturing fluid were experimentally investigated, and the effects of interfacial tension, (IFT) permeability, oil viscosity, and the salinity of the imbibition flui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…Figure 6 shows that the imbibition recovery changes with permeability and IFT. It shows that the imbibition rate and recovery increase with an increase in permeability, 42,45,46,117 which is attributed to many pores with a large size and the good connectivity among pores in a high-permeability core.…”
Section: Governing Factors Of Eor By Imbibitionmentioning
confidence: 98%
See 1 more Smart Citation
“…Figure 6 shows that the imbibition recovery changes with permeability and IFT. It shows that the imbibition rate and recovery increase with an increase in permeability, 42,45,46,117 which is attributed to many pores with a large size and the good connectivity among pores in a high-permeability core.…”
Section: Governing Factors Of Eor By Imbibitionmentioning
confidence: 98%
“…In general, the permeability is directly proportional to porosity, and a larger permeability means a larger pore size and better connectivity among pores. 46 A large pore size and good connectivity among pores decrease the flow resistance of a fluid, which is favorable to the imbibition of water and the expelling of oil. 42 However, the capillary pressure will be small when pores are large (eq 1b), and thus, the imbibition recovery will decrease.…”
Section: Governing Factors Of Eor By Imbibitionmentioning
confidence: 99%
“…Bing et al conducted spontaneous imbibition experiments on tight sandstone cores in 0.21% to 2.1%TDS brine and found that oil production from imbibition in 0.21% TDS brine increased rapidly, resulting in a 4.5% increase in oil recovery [15]. Ren et al believed that the saturation of the core with high-salinity imbibition can effectively hinder the water sensitivity of the rock sample, thereby avoiding the decrease of core permeability [16]; Chavan et al found that the oil imbibition recovery is the highest in the salinity range of injected water with TDS of 2000 ppm~5000 ppm, and the composition of the reservoir brine has a significant influence on the optimal salinity of injected water [17].…”
Section: Introductionmentioning
confidence: 99%
“… 33 Guo and Ren noted that there is a certain optimal interfacial tension that reduces the amount of bypassed oil in the formation, resulting in the highest imbibition recovery, rather than a lower interfacial tension corresponding to the higher oil recovery. 34 , 35 Jing et al studied the influence of matrix permeability, temperature, pressure, pore size, and fracture density on the degree of dynamic imbibition production; a normalized model of the dimensionless imbibition recovery degree is obtained using dimensionless experimental parameters. 36 However, previous studies mainly considered the impact of a fracturing fluid on rock surface tension after fracturing, without considering the effect of spontaneous imbibition of the fracturing fluid on improving the oil displacement efficiency during the shut-in process, after fracturing fluid injection.…”
Section: Introductionmentioning
confidence: 99%
“…In cores with different pore structure combinations, the ratio of medium to large pore throats determines the effect of spontaneous imbibition and oil displacement; residual oil is mainly retained in the microporous throats. , Cheng, Lai et al investigated the influence of gravity and pore throat structure on the imbibition effect during the imbibition process and noted that the nanopore throat is the main imbibition point. , In previous studies, scholars have mainly used the mass and volume methods to conduct imbibition experiments, exploring the factors that affect imbibition and displacement; however, these experiments were mostly based on formation water. , Adding surfactants to the fracturing fluid to change the wettability and reduce the interfacial tension can effectively improve the oil recovery after fracturing reformation. Based on the mass method experiment, it was found that the degree of salinity is negatively correlated with spontaneous imbibition recovery; , fractures can effectively expand the imbibition area of the dense matrix in contact with water, thereby increasing the recovery and imbibition rate . Guo and Ren noted that there is a certain optimal interfacial tension that reduces the amount of bypassed oil in the formation, resulting in the highest imbibition recovery, rather than a lower interfacial tension corresponding to the higher oil recovery. , Jing et al studied the influence of matrix permeability, temperature, pressure, pore size, and fracture density on the degree of dynamic imbibition production; a normalized model of the dimensionless imbibition recovery degree is obtained using dimensionless experimental parameters . However, previous studies mainly considered the impact of a fracturing fluid on rock surface tension after fracturing, without considering the effect of spontaneous imbibition of the fracturing fluid on improving the oil displacement efficiency during the shut-in process, after fracturing fluid injection.…”
Section: Introductionmentioning
confidence: 99%